Hindu Nationalism and the Converging, Diverging and Intersecting Identities of Caste and Race in India: Dialogue, Dilemma and Discourse - Guha, Ayan (Journal of Asian and African studies, 2025)
This essay unpacks how Hindu nationalism has understood the concepts of caste and race through its ideologues? textual strategies. It is divided into three sections. The initial section uncovers how Hindu nationalism?s dialogue with the colonial framework of knowledge produced several conceptual dilemmas inconsistent with its core objectives. The second part demonstrates how to counter such dilemmas proponents Hindu nationalists indulged in myriad intellectual manoeuvres to arrive at such notions of the interrelationship between caste and race, which are complimentary to its principal agenda. The final section unravels how their intellectual strategies produced a largely conservative outlook of passive reformism.